DEVELOPMENT OF GRAIN PROCESSING ENTERPRISES BASED ON THE CLUSTER SYSTEM IN UZBEKISTAN - Alimov Gayratjon Abdurakhmon ugli (Galaxy International Interdisciplinary Research Journal, 2024)
The article focuses on the organization of grain clusters in Uzbekistan, as well as the organizational and theoretical aspects of the role of this system in the agriculture of our country, where there are some problems that the author proposes to solve through cluster networks and the socio-economic situation.